2023
DOI: 10.3389/fmed.2023.1264846
|View full text |Cite
|
Sign up to set email alerts
|

Real-world post-deployment performance of a novel machine learning-based digital health technology for skin lesion assessment and suggestions for post-market surveillance

Lucy Thomas,
Chris Hyde,
Dan Mullarkey
et al.

Abstract: IntroductionDeep Ensemble for Recognition of Malignancy (DERM) is an artificial intelligence as a medical device (AIaMD) tool for skin lesion assessment.MethodsWe report prospective real-world performance from its deployment within skin cancer pathways at two National Health Service hospitals (UK) between July 2021 and October 2022.ResultsA total of 14,500 cases were seen, including patients 18–100 years old with Fitzpatrick skin types I–VI represented. Based on 8,571 lesions assessed by DERM with confirmed ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…By location, the two studies [46,47] published by Australian authors reported comparatively lower sensitivity values in CNNs than previously reported [39][40][41][43][44][45]48,49]. Australia remains the nation with the highest incidence of melanoma [2].…”
Section: Performance Of Bedside Cnn Versus Cliniciansmentioning
confidence: 82%
See 2 more Smart Citations
“…By location, the two studies [46,47] published by Australian authors reported comparatively lower sensitivity values in CNNs than previously reported [39][40][41][43][44][45]48,49]. Australia remains the nation with the highest incidence of melanoma [2].…”
Section: Performance Of Bedside Cnn Versus Cliniciansmentioning
confidence: 82%
“…There were 11 articles [39][40][41][42][43][44][45][46][47][48][49] which reported performance on bedside CNNs. One article's [42] main outcome was monitoring changes in sequential digital dermatoscopy and presented results differently and could not be compared.…”
Section: Assessment Of Performance Metrics Cnnmentioning
confidence: 99%
See 1 more Smart Citation